Der Mensch als natürliches und künstliches Wesen - Havlíček, Aleš (ΠΗΓΗ/FONS, 2016)
This article traces the heritage of the Aristotelian political investigations in Thomas Hobbes’s Leviathan. It can be very important to note that the definition of man as a “social” animal will develop in Hobbes’s characterization by the opposite terms, the “natural” man and man “artifact”; two adjectives that Hobbes uses instead of “political”, the very Aristotelian adjective.
Keywords: Aristotels’s Politics; Thomas Hobbes’s Leviathan; “Social/Political” Animal